Performance Management: a Seven Country Study - Alan R. Nankervis (Universitas Trisakti, 2006)
Of all the human resource management (HRM) processes performance management (PM) is potentially the most powerful, yet simultaneoustly the most problematic. This paper reports the findings of a recent research study of the usage, characteristics, and effectiveness of performance management systems across seven countries in the Asia Pacific region. Australia, Indonesia, Singapore, Thailand, Hong Kong, the Philippines, and Sri Lanka were surveyed. Whilst the sample sizes were widely divergent, ranging from only eight responses in Sri Lanka to almost one thousand in Australia, the themes which emerged are interesting not only for their similarities but also for their contextual differences. There are some signs of an increasing convergence between system types and usage, but as expected, this trend is undoubtedly mediated by specific socio-cultural differences.